Corporate strategies for Maxim's Tea House - Garcia, Kenneth Mark F. (Animo Repository, 1997)
Maxims Tea House operates as a full-service restaurant offering a wide variety of Chinese cuisine. Established in 1978, Maxims Tea House chose to niche into a specific subsegment of the restaurant industry, as an upscale yet casual Chinese restaurant serving the middle socioeconomic groups. Since then, Maxims has grown into 8 restaurant branches and 10 fastfood outlets in Metro Manila. Inspite the evident success of Maxims, the company had learned how to survive in such a fragmented industry, where competition continues to stiffen, without any formal and organized systems. Given the companys objective to be the largest complete Chinese restaurant in the country, this paper was tasked to analyze its current position and to come up with competitive strategies suited to its environment. This is done with a concrete company study and an industry analysis as well. Findings reveal that due to the entrepreneurial point of view of management, Maxims remained to be the typical Chinese family-owned business entity. It has no formal and organized systems for operations, marketing and even in financial aspects. For this reason, to some extent controlling and planning has always been informal among family members and would require more attention. For a business concern generating annual gross revenues of more than P200 million and netting out profits of about P25 million, the absence of a formal system would expose the firm to undue risks. Being a fragmented industry, Maxims is faced with stiff competition from numerous existing players. More particularly, the company has to contend with rivalry from the more popular food service outfits such as Chowking, Ling Nam and Ma Mon Luk. Noteworthy, though, the company was able to be one of the top 15 food service service companies in the country. And market studies point to an even more promising and prosperous business for the company. Based on projected population growth, the food service business is foreseen to expand to a P65 billion industry by the year 2000. Also, industry sources reveal that among the types of restaurants in the market, the Chinese cuisine is the second preference of the consumers, closely following the Filipino dishes. In view of the said prospects, it is imperative for the company to give due attention to key factors such as the quality and prices of its products/services among others. To do this, it is recommended that the company adopts differentiation strategies that would focus on its image, support and quality. This will be implemented by adopting strategies such as decentralization and increased value-added, among others, to cope with the concerns of a fragmented industry. The company should have an aggressive marketing plan to boost its market share. Improved image and market awareness should be given more emphasis. It is further recommended that the company should shy away from franchising and concentrate more on other forms of expansion. Internally, the company should come up with organized planning and controlling systems to improve its competitiveness. Ultimately, by doing all of the said imperatives, the company is expected to achieve its objectives.